From Garden to Marketplace: Teologi Kristen tentang Kerja, Panggilan, dan Kesejahteraan Ekonomi - Purwanto, Edi (Jurnal Teologi Praktika, 2025)
This article presents a systematic literature review (SLR) using the PRISMA framework to explore how Evangelical Christian theology interprets work, vocation, wealth, and economic flourishing. Drawing upon scholarly sources from the Scopus database, this study synthesizes theological reflections on the biblical foundation of work, ethical perspectives on wealth, and the socio-spiritual implications of economic life. The findings reveal that work is not merely a means of livelihood but a divine calling that reflects God’s creative image. Wealth is seen not as an end but as a trust in God, requiring responsible stewardship and social accountability. The concept of flourishing in Christian theology centers on participation in God’s redemptive mission through meaningful work, generous giving, and transformative community engagement. This study highlights the need for a renewed theological framework that integrates faith and economics, equipping the church to respond prophetically to modern economic challenges